Investigating Virological, Immunological, and Pathological Avenues to Identify Potential Targets for Developing COVID-19 Treatment and Prevention Strategies - Zafar Mahmood (Vaccines, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging coronavirus causing respiratory disease commonly known as COVID-19. This novel coronavirus transmits from human to human and has caused profound morbidity and mortality worldwide leading to the ongoing pandemic. Moreover, disease severity differs considerably from individual to individual. Investigating the virology of COVID-19 and immunological pathways underlying its clinical manifestations will enable the identification and design of effective vaccines and potential therapies. In this review, we explore COVID-19 virology, the contribution of the immune system (innate and adaptive) during infection and control of the virus. Finally, we highlight vaccine development and implications of immune system modulation for potential therapeutic interventions to design better therapeutic strategies to guide future cure.